2009
DOI: 10.1007/s00167-008-0703-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic, clinical and arthroscopic study of the discoid meniscus variant in Greek population

Abstract: This retrospective study was aimed to investigate the epidemiologic, clinical and arthroscopic features of discoid meniscus variant in Greek population. We reviewed the cases of 2,132 patients who underwent knee arthroscopy between 1986 and 2004 and diagnosis of discoid lateral meniscus was established in 39 patients with mean age of 31.7 +/- 9.4 years old. Incidence of the discoid lateral meniscus variant was recorded at rate of 1.8% presenting no significant differences according to patient gender or lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 42 publications
4
36
0
1
Order By: Relevance
“…Furthermore, they proposed that if the discoid meniscus is torn, this cartilage wear and degeneration will occur quickly and deteriorate the clinical results. Similarly, Papadopoulos et al [3] reported that intact DLM cases showed better clinical results compared to torn DLM in their series. Asik et al [14] compared the clinical outcomes according to the tear type and found reduced satisfactory outcomes in patients with complex meniscal tears.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, they proposed that if the discoid meniscus is torn, this cartilage wear and degeneration will occur quickly and deteriorate the clinical results. Similarly, Papadopoulos et al [3] reported that intact DLM cases showed better clinical results compared to torn DLM in their series. Asik et al [14] compared the clinical outcomes according to the tear type and found reduced satisfactory outcomes in patients with complex meniscal tears.…”
Section: Discussionmentioning
confidence: 90%
“…drozkankose@hotmail.com however, the incidence of DLM is reported between 0.4 and 16.6 % in patients who underwent knee arthroscopy [3,4]. Clinical manifestations of lateral discoid meniscus are highly variable depending on the type of the discoid meniscus, the presence of an accompanying tear and the status of rim stability.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…also found knee pain to be the dominant symptom in 90% of cases. (6,36,37,39) Changes in the morphology and vascularization of DLM render the condition more prone to mechanical stress; therefore, arthroscopic findings of combined meniscus lesions are relatively common. (33) We detected DLM combined with lesions of the meniscus itself in 11 (85.72%) cases, and the incidence was statistically higher in patients over the age of 18 (90%).…”
Section: Discussionmentioning
confidence: 99%
“…(3) Thus far, research has indicated the existence of clear racial differences in the incidence of this morphological anomaly, with the Asian population exhibiting the highest incidence (from 9.1% to 16.6%), while the European population demonstrates a somewhat lower incidence of DLM (from 0.4% to 5%). (4,5,6) In 1979, Watanabe et al established a classification system in which DLM was divided into three groups: complete (a), incomplete (b) and Wrisberg type (c), and, in 1998, Monllau et al suggested adding "ring-shaped" lateral meniscus (d) as the fourth group in this classification. (7,8) The most common lesions are complete and incomplete, which are usually asymptomatic and represent incidental findings unless combined with meniscus lesions.…”
Section: Introductionmentioning
confidence: 99%